Inhibition of GlcNAc-processing glycosidases by C-6-azido-NAG-thiazoline and its derivatives - Krejzová, Jana; Simon, Petr; Kalachova, Lubica; Kulik, Natallia; Bojarová, Pavla; Marhol, Petr; Pelantová, Helena; Cvačka, Josef; Ettrich, Rüdiger; Slámová, Kristýna; Křen, Vladimír (Molecules (Basel, Switzerland), 2014)
NAG-thiazoline is a strong competitive inhibitor of GH20 β-N-acetyl- hexosaminidases and GH84 β-N-acetylglucosaminidases. Here, we focused on the design, synthesis and inhibition potency of a series of new derivatives of NAG-thiazoline modified at the C-6 position. Dimerization of NAG-thiazoline via C-6 attached triazole linkers prepared by click chemistry was employed to make use of multivalency in the inhibition. Novel compounds were tested as potential inhibitors of β-N-acetylhexosaminidases from Talaromyces flavus, Streptomyces plicatus (both GH20) and β-N-acetylglucosaminidases from Bacteroides thetaiotaomicron and humans (both GH84). From the set of newly prepared NAG-thiazoline derivatives, only C-6-azido-NAG-thiazoline displayed inhibition activity towards these enzymes; C-6 triazole-substituted NAG-thiazolines lacked inhibition activity against the enzymes used. Docking of C-6-azido-NAG-thiazoline into the active site of the tested enzymes was performed. Moreover, a stability study with GlcNAc-thiazoline confirmed its decomposition at pH < 6 yielding 2-acetamido-2-deoxy-1-thio-α/β-D-glucopyranoses, which presumably dimerize oxidatively into S-S linked dimers; decomposition products of NAG-thiazoline are void of inhibitory activity.
Keywords: Protein Binding; molekulární konformace; acetylglukosamin; Models, Molecular; Molecular Conformation; stabilita léku; Catalytic Domain; glykosidhydrolasy; beta-N-acetylhexosaminidasy; Glycoside Hydrolases; thiazoly; Acetylglucosamine; Drug Stability; Thiazoles; katalytická doména; molekulární modely; vazba proteinů; beta-N-Acetylhexosaminidases